2009
DOI: 10.1590/s1516-35982009000600015
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da suplementação de enzima fitase sobre o metabolismo de nutrientes e o desempenho de poedeiras

Abstract: Avaliou-se o efeito da adição da enzima fitase sobre o desempenho e o metabolismo de poedeiras comerciais. Foram utilizadas 360 poedeiras da linhagem Bovans Goldline, distribuídas em delineamento inteiramente casualizado, com 12 repetições de 6 aves por unidade experimental e 5 tratamentos, que consistiram de cinco dietas: controle positivo; controle negativo (CN) com 0,15% de fósforo disponível; CN + 200 FTU de fitase; CN + 400 FTU de fitase; CN + 600 FTU de fitase. A dieta controle positivo foi formulada seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
2
5
0
2
Order By: Relevance
“…In the present reseach, unlike egg production, egg weight remained unchanged when phytase was added or even when dLys content varied F 12,169 = 1.44, p = 0.15, although both factors have been stated to positively influence egg weight. 29,31 Only, egg weight was higher in hens fed the phytase-free diet containing 0.25 % avP than the average of those fed diets with 0.12 % avP F 12,169 = 3.70, p = 0.06, as also reported by Ceylan et al 32 and Englmaierová et al 33 , but in contrast from studies by Augspurger et al, 34 Lim et al, 21 and Viana et al 35 ( Table 3).…”
Section: Resultssupporting
confidence: 63%
“…In the present reseach, unlike egg production, egg weight remained unchanged when phytase was added or even when dLys content varied F 12,169 = 1.44, p = 0.15, although both factors have been stated to positively influence egg weight. 29,31 Only, egg weight was higher in hens fed the phytase-free diet containing 0.25 % avP than the average of those fed diets with 0.12 % avP F 12,169 = 3.70, p = 0.06, as also reported by Ceylan et al 32 and Englmaierová et al 33 , but in contrast from studies by Augspurger et al, 34 Lim et al, 21 and Viana et al 35 ( Table 3).…”
Section: Resultssupporting
confidence: 63%
“…Lan et al (2002), when analyzing the metabolizable energy content in the corn and soybean based feed supplemented with phytase enzyme (250-1000 uft kg -1 ) for Avian chickens in the initial and final phases, found higher values of apparent metabolizable energy when compared to a diet with normal levels of phosphorus and without enzyme supplementation. Dourado et al (2007) found that phytase provided the greatest increase in true metabolizable energy corrected for nitrogen balance (TMEn) of corn compared with other enzymes in broilers diets, in which we observed improvement of 95 kcal kg-1 in TMEn adding phytase, while Viana et al (2009) studying laying hens, reported that the addition of enriched phytase provides increased metabolism of energy and energy corrected by nitrogen balance.…”
Section: Resultssupporting
confidence: 50%
“…Sunflower meal is rich in fiber and phytic acid, and therefore, a positive effect with the addition of the enzyme complex in the diets was expected; however, no such effect was verified in the present experiment. Liu et al (2007) and Viana et al (2009) also verified that the addition of phytase to diets with reduced nutrient levels did not improve egg production, egg weight, or feed conversion per dozen eggs of layers. The results of these authors were very similar to those found in the present study, where no influence of enzyme complex on those parameters were detected.…”
Section: Sunflower Meal and Supplementation Of An Enzyme Complex In Lmentioning
confidence: 77%